2021
DOI: 10.1002/jrs.6162
|View full text |Cite
|
Sign up to set email alerts
|

Space weathering simulation of micrometeorite bombardment on silicates and their mixture for space application

Abstract: Missions to planetary bodies require innovative techniques for the in situ investigation of their surfaces, especially when landings are planned. Therefore, Raman spectroscopy as an excellent laboratory tool for rapid mineralogical analysis of both terrestrial and extraterrestrial rocks has been successfully proposed for the investigation of planetary surfaces. Examples are the Raman laser spectrometer (RLS) of the joint ESA and Roscosmos mission ExoMars 2022 as well as Scanning Habitable Environments with Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…After laser irradiation, the wavenumber, shape, and FWHM of the doublet peaks did not change substantially (Table A.3). The newly formed np-Fe 0 particles are pure metallic iron that have no Raman effects, and the potential reduction of the fluorescence-dominated background due to the formation of np-Fe 0 may facilitate a better interpretation of the individual mineral peaks by the Raman spectrometer (Weber et al 2021(Weber et al , 2022. Amorphization of the olivine surface may cause local disorder and result in the broadening of Raman peaks, as suggested in previous studies (Rouquette et al 2008;Santamaria-Perez et al 2016); however, the amorphous layer showed no substantial influence in our experiments.…”
Section: Raman Spectral Characteristics Of Altered Olivinementioning
confidence: 99%
“…After laser irradiation, the wavenumber, shape, and FWHM of the doublet peaks did not change substantially (Table A.3). The newly formed np-Fe 0 particles are pure metallic iron that have no Raman effects, and the potential reduction of the fluorescence-dominated background due to the formation of np-Fe 0 may facilitate a better interpretation of the individual mineral peaks by the Raman spectrometer (Weber et al 2021(Weber et al , 2022. Amorphization of the olivine surface may cause local disorder and result in the broadening of Raman peaks, as suggested in previous studies (Rouquette et al 2008;Santamaria-Perez et al 2016); however, the amorphous layer showed no substantial influence in our experiments.…”
Section: Raman Spectral Characteristics Of Altered Olivinementioning
confidence: 99%
“…As it has been mentioned before, the development of the science for the preparation of the mentioned missions is a hard but very important task. In this sense, Weber et al [ 6 ] emphasized that missions to planetary bodies require innovative techniques for the in situ investigation of their surfaces, especially when landings are planned, and state that Raman spectroscopy as an excellent laboratory tool for rapid mineralogical analysis of both terrestrial and extraterrestrial rocks. However, when preparing such space missions, it is essential to be prepared for all possible outcomes, such as samples exhibiting space weathering (SW).…”
Section: The Importance Of Mars and Space Exploration By Raman Spectr...mentioning
confidence: 99%
“…13,14 PL is generally expected to be inherent for various planetary surfaces and can be affected at those with dilute atmospheres, that is, strong space weathering. 15 Different spectroscopic techniques were explored in order to suppress PL in Raman spectra; see for detailed description the review 16 : time-resolved, shifted excitation wavelength difference, surface enhanced, photobleaching, and many other techniques. All these approaches have their critical limitations and are addressed to an attempt to resolve RS at the presence of strong PL rather than to avoid PL excitation/detection.…”
Section: Introductionmentioning
confidence: 99%
“…PL has a pure electronic nature, resulting from radiative transitions between electronic states, representing both a material matrix and also abundant impurities; some of those are strong luminescent centers: for instance, ions of transition metals or rare earth elements 13,14 . PL is generally expected to be inherent for various planetary surfaces and can be affected at those with dilute atmospheres, that is, strong space weathering 15 . Different spectroscopic techniques were explored in order to suppress PL in Raman spectra; see for detailed description the review 16 : time‐resolved, shifted excitation wavelength difference, surface enhanced, photobleaching, and many other techniques.…”
Section: Introductionmentioning
confidence: 99%